Mother, Madonna, Whore : the Idealization and Denigration of Motherhood. - Welldon, Estela (Karnac Books, 1992)
Welldon explores why the quality of their bodies is fundamental to women's psychology; how this may lead to self-mutilation; and how such perverse behavior may also be aimed at objects which women see as their own creations, specifically, their babies. The potential causes and consequences of these conditions, including maternal and paternal incest and its frequent aftermath, prostitution, are also discussed.